No Experimental Evidence For Yawn Contagion In Galahs (Eolophus Roseicapilla) - Jonas C. P. van Oosten; Lisa-Claire Vanhooland; Tom S. Roth; Andrew C. Gallup; Jorg J. M. Massen (Animal Behavior and Cognition)
Yawning is a ubiquitous behavior among vertebrates, yet evidence for yawn contagion is sparce. Nevertheless, over the past decade yawn contagion has been documented in an increasing number of species. Still, quite some studies fail to show yawn contagion in other species. The lack of contagious yawning in some species, but not in others, raises questions about the evolutionary origin and adaptive function of this response. Yet, the restricted research focus on mostly social mammals limits its explanatory value on an evolutionary scale. Yawn contagion is relatively understudied outside mammalian species, and so far, yawn contagion has only been documented in one bird species: budgerigars (Melopsittacus undulatus). To allow a more comparative approach, also among birds, we studied the presence of contagious yawning in another, highly social, bird species, the galah (Eolophus roseicapilla). We presented video stimuli composed of yawn footage and non-yawn control footage to fifteen captive galahs in two different studies differing in the size and number of repetitions of the on-screen stimuli, while also taking into account approximations of visual attention and the affiliation strength with the on-screen individual. We found no evidence for yawn contagion in galahs in either study, which contrasts with findings in budgerigars. Budgerigars and galahs do, however, have a highly similar socio-ecology and the methods used to test for yawn contagion were highly similar too. Although more work is needed, these combined results therefore underline earlier findings of convergent evolution of contagious yawning in mammals and birds, yet suggest that it happened in very restrictive lineages only. The specific selection pressures that have contributed to the evolution of this trait in this select group of animals remain obscure.